KUALITAS SUMBER DAYA APARATUR DALAM MENCAPAI TUJUAN PEMBANGUNAN DI DISTRIK YAMO, KABUPATEN PUNCAK JAYA PROVINSI PAPUA - Yoman, Mesina; Pratiknjo, Maria Heny; Tasik, Femmy (JURNAL ADMINISTRASI PUBLIK, 2016)
Implementation of development in the district of Puncak Jaya regency Yamo stillfound the existence of some constraints affecting the effectiveness of work among employees.Constraints in question concerns the improvement of the quality of personnel resources thatare not optimal so that needs to be improved through education, training and staffing inorder to perceive the efforts made in the quality of personnel resources to achievedevelopment goals Yamo District of Puncak Jaya. Type of study used a descriptive studyusing informants determination by purposive sampling, and data collection techniques donein the form of interviews, and literature. Data analysis techniques used qualitatively to makethe transcript then arranged in a matrix form and then analyzed using content analysismethod of data reduction. The results showed that the quality of personnel resources on civilservants in the District Yamo Puncak Jaya regency is very low resulting in productivity didnot correspond with the expectations of society that need special attention from the localgovernment through the development of education, training, and placement of the rightemployees to improve the quality of the source human.Keywords: Resources Quality Apparatus, Interest pembagunan, Yamo District